Functional and Topological Studies with Trp-Containing Analogs of the Peptide StII(1-30) Derived From the N-Terminus of the Pore Forming Toxin Sticholysin II: Contribution to Understand its Orientation in Membrane - Ros, Uris; Souto, Ana Lucia C. F.; Oliveira, Felipe J. de; Crusca, Edson [UNESP]; Pazos, Fabiola; Cilli, Eduardo Maffud [UNESP]; Lanio, Maria E.; Schreier, Shirley; Alvarez, Carlos (Wiley-Blackwell, 2013)
Sticholysin II (St II) is the most potent cytolysin produced by the sea anemone Stichodactyla helianthus, exerting hemolytic activity via pore formation in membranes. The toxin's N-terminus contains an amphipathic alpha-helix that is very likely involved in pore formation. We have previously demonstrated that the synthetic peptide StII(1-30) encompassing the 1-30 segment of St II forms pores of similar radius to that of the protein (around 1 nm), being a good model of toxin functionality. Here we have studied the functional and conformational properties of fluorescent analogs of StII(1-30) in lipid membranes. The analogs were obtained by replacing Leu residues at positions 2, 12, 17, and 24 with the intrinsically fluorescent amino acid Trp (StII(1-30L2W), StII(1-30L12W), StII(1-30L17W), or StII(1-30L24W), respectively). The exchange by Trp did not significantly modify the activity and conformation of the parent peptide. The blue-shift and intensity enhancement of fluorescence in the presence of membrane indicated that Trp at position 2 is more deeply buried in the hydrophobic region of the bilayer. These experiments, as well as assays with water-soluble or spin-labeled lipid-soluble fluorescence quenchers suggest an orientation of StII(1-30) with its N-terminus oriented towards the hydrophobic core of the bilayer while the rest of the peptide is more exposed to the aqueous environment, as hypothesized for sticholysins. (C) 2013 Wiley Periodicals, Inc.
Keywords: sticholysin; pore-forming toxin; Trp-containing peptides; transbilayer orientation; fluorescence